Evidence for Site-Specific, Systematic Adaptation of Substance Prevention Curriculum With High Risk Youth in Community and Alternative School Settings - Holleran Steiker, Lori K. (2014)
The problem of substance use among older youth is of great concern, but has received little attention in prevention research. This may be due to the perception that prevention programming is developmentally inappropriate for older youth who are actively experimenting with substances. This project examined the differential effectiveness of youth-driven adaptations of the evidence-based prevention program, keepin’ it REAL (KiR). The participating sites included a juvenile justice day program, a homeless shelter, four alternative high schools, low-income housing programs, an LGBTQ youth center, and a youth group on the Texas-Mexico border. In the project’s first phase, high risk youth in community settings tailored KiR workbooks and videos to increase the relevance for their peers, older adolescents who are likely to have already initiated drug use. The second phase of the study, discussed here in detail, evaluates the effectiveness of the adapted versions of KiR compared with the original version and a comparison condition. The study employed a quasi-experimental pretest posttest design with a 6-week follow-up. Youth also participated in focus groups. Both qualitative and quantitative data suggest that participants receiving the adapted version of the curriculum experienced greater improvement in acceptance and use of substances than youth in the other two groups.